O diário na formação de professores - Cunha, Silvia Cacace (2009)
The present work investigates the exercise of the register in the práxis of the teacher and the artist, a time that the research transits in the universe of the Visual Arts. The dissertation presents a case study that it searchs to understand a process of social representation through the registers of moments of the personal and professional history of a teacher of Visual Arts and a plastic artist contemporary; pointing out the importance of the register in the práxis of the citizens that are inserted in the field of the Education and the Visual Arts. The representations and speeches of the two citizens had been analyzed through the technique of Bardin (1977), content analysis, where it was possible to identify excellent aspects of the formation of the two citizens, understanding inside of social, cultural and historical the context that they are inserted. The paper of the art as register and the wakening for visual language as form of possible communication if made excellent for the boarding of this research. In this context, to verify the paper of the register in the programs of formation of professors and other professionals, in special the artist, who search other looks, new challenges, perceiving the importance and the wealth of the register document as a form to keep our history. This research does not have the pretension to conclude, to generalize. For the the opposite, it is intended to congregate action, to register, to show and to point possible trajectories in relation to the formation of art teachers and to presents so that it can be visited, searched for all those that if to interest.